Optimization of puffed corn-fish snack extrusion conditions using response surface methodology - Shahmohammadi, Hamid Reza; Bakar, Jamilah; Abdul Rahman, Russly; Mohd Adzahan, Noranizan (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2016)
To optimize the extrusion conditions of novelty developed puffed corn-fish snack, Response Surface Methodology was performed. Feed rate (810-1206 g/min), temperature (105-125ºC) and screw speed (146- 208 rpm) were considered as 3 independent variables. Expansion ratio, density, sensory texture, overall acceptability, linear distance and count peak were used as dependent variables. Density and expansion ratio were significantly (p < 0.05) correlated with the factors (R2 > 0.94). Optimum condition was found at 116ºC, feed rate at1107 g/min and screw speed at 148 rpm, where the expansion ratio of 5.5 and density of 41.92 kg/m3 were obtained. Besides, the effect of feed rate (0.5-1.5 kg/min) on textural properties was individually studied. A quadratic model (R2 >0.95) was found for expansion ratio versus feed rate while density showed a cubic regression model (R2 >0.80) verses feed rate.